The Arab electronic medical journals: an evaluation study. - محمود, إكرام (Iraqi National Journal of Nursing Specialties, 2011)
Objective: The aims of research to identify sample of websites of Arabian medical periodicals and exam applying tostandards for publishing on the internet.Methodology: A survey method is applied about nine medical periodicals websites and data are collected throughforms include five international standards to assessing websites.Results: of data collected, the following findings are obtained:1. Through examining website addresses, unsuitability was found in using Universal Resources Locater, because six ofperiodicals use com. in URL. While, all of them not relevance commercial but scientific aim.2. To measure Credibility Standard by adopting numbers values, the results found, four of periodicals obtained (level 5from 6) and Annals of Saudi Medicine obtain (level 6 from 6). While, two periodicals were poor in Credibility (level 2).3. In Information Recourse Form, four of periodicals were found to display their information in different forms, andfive of them display information in titles, abstracts and full text, and six from their publish in electronically form aswell as paper form.Recommendations: The study presents many of recommendations to websites publishers